1992
DOI: 10.1177/002203459207100s09
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fluoride Measurements for Estimation of the Anti-caries Efficacy of Fluoride Treatments

Abstract: The aims of this work were (a) to assess the oral bioavailability of fluoride delivered from dentifrices and (b) to test for a possible link between the results and clinical data obtained with the same dentifrices. Oral fluoride concentrations were measured in samples of saliva and plaque taken from seven subjects, after use of dentifrices which contained 0, 1000, 1500, and 2500 micrograms F/g as sodium monofluorophosphate. Salivary fluoride in samples obtained within the first few hours after a single dentifr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
3
31
0
4
Order By: Relevance
“…7,8,14,15,25,26,30 In these studies, fluoride measurements were taken on saliva samples collected 6-24 h after the regular daily use of fluoride products, brushing with a fluoride dentifrice, and/or using fluoride mouthrinsing. Most of these studies reported that the fluoride concentrations in saliva remained significantly elevated, over a period of 12-24 h, compared with the baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,14,15,25,26,30 In these studies, fluoride measurements were taken on saliva samples collected 6-24 h after the regular daily use of fluoride products, brushing with a fluoride dentifrice, and/or using fluoride mouthrinsing. Most of these studies reported that the fluoride concentrations in saliva remained significantly elevated, over a period of 12-24 h, compared with the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…dental exposure to low and steady fluoride concentrations via oral fluids. 7,8 An increase in the fluoride concentration in saliva from 0.01 to 0.1 ppm, i.e., a 5-to 10-fold increase, for prolonged periods may be very effective for caries control.…”
mentioning
confidence: 99%
“…This suggests that only small particles that nucleated and/or penetrated into the pores in the early time interval were fixed inside the pores by their further growth and aggregation. Duckworth, et al 5 (1992) observed an increase in salivary fluoride levels with increasing fluoride dentifrice concentration (0, 1000, 1500, and 2500 ppm F as SMFP) after a single dentifrice application or after a fourweek daily use. In this sense, if the treatment time of the present study was increased to at least one week, it is possible that a positive correlation could have been found in enamel fluoride uptake and in the salivary fluoride after using a fluoridated dentifrice preceded by a rinse with a CaCl 2 solution.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of fluoride toothpaste use: salivary fluoride levels Research by Duckworth and colleagues had shown that the equilibrium baseline fluoride salivary concentration at 18-hour post-brushing was higher among regular users of fluoride toothpaste than among others (Duckworth et al 1992, Duckworth and Stewart 1994, Toumba and Curzon 2001. It was decided therefore to use saliva fluoride concentration as a quantitative method of assessing the children's toothbrushing with fluoride toothpaste behaviour.…”
Section: Questionnaire Administrationmentioning
confidence: 99%